Structural analysis of human Orc6 protein reveals a homology with transcription factor TFIIB - Liu, Shixuan; Balasov, Maxim; Wang, Hongfei; Wu, Lijie; Chesnokov, Igor N; Liu, Yingfang (Proceedings of the National Academy of Sciences - PNAS, 2011)
The Origin Recognition Complex (ORC) is a six-subunit protein important for the initiation of DNA replication in eukaryotic cells. Orc6 is the smallest and the least conserved among ORC subunits. It is required for the DNA replication but also has a function in cytokinesis in metazoan species, however, the mechanisms of Orc6 action in these processes are not clear. Here we report a structure of the middle domain of human Orc6. This domain has an overall fold similar to the corresponding helical domain of transcription factor TFIIB. Based on these findings, a model of Orc6 binding to DNA is produced. We have identified amino acids of Orc6 which are directly involved in DNA binding. Alterations of these amino acids abolish DNA binding ability of Orc6 and also result in reduced levels of DNA replication in vitro and in cultured cells. Our data indicate that Orc6 is one of the DNA binding subunits of ORC in metazoan species. We propose that Orc6 may participate in positioning of ORC at the origins of DNA replication similar to the role of TFIIB in positioning transcription preinitiation complex at the promoter.